Comparison of Measures adopted to combat COVID 19 Pandemic by different countries in WHO regions - DB, Shubha; Undi, Malathesh; Annadani, Rachana; Siddique, Ayesha (Indian Journal of Community Health, 2020)
Since the emergence of Corona Virus Disease 19 (COVID 19) in China in December 2019, a lot of significant decisions have been taken by the World Health Organization (WHO) and several countries across the globe. As the world reels under the threat of rapid increase in the number of cases and is planning strategies with the limited information available on the virus, it is essential to learn from the experience of countries across the globe. Hence, we selected a few countries in five WHO regions based on their COVID 19 caseload, management strategies and outcome and compared some of the important measures taken by them to contain the spread of infection. Strategies like extensive testing and contact tracing, strict quarantine and isolation measures, Hospital preparedness, complete restriction of non-essential travel, strict border control measures and social distancing measures play a vital role in containment of the spread. All the countries faced the novel strain of virus and implemented similar strategies as per the guidance of WHO, but the extent of preparedness, swiftness with which the decisions were made and the scale of measures made the difference.